Wage Effects of High-Skilled Migration : International Evidence - Grossmann, Volker; Stadelmann, David (World Bank, Washington, DC, 2013)
The international migration of high-skilled workers may trigger productivity effects at the macro level such that the wage rate of skilled workers increases in host countries and decrease in source countries. The authors exploit data on international bilateral migration flows and provide evidence consistent with this theoretical hypothesis. They propose various instrumentation strategies to identify the causal effect of skilled migration on log differences of GDP per capita, total factor productivity, and the wages of skilled workers between pairs of source and destination countries. These strategies aim to address the endogeneity problem that arises when international wage differences affect migration decisions.